Perbuatan Kohabitasi Dalam Pasal 415 Dan 416 Undang Undang Nomor 1 Tahun 2023 Tentang Kitab Undang Undang Hukum Pidana - Hidayatulloh, Muhammad Dani (Peneliti.net, 2024)
The government together with the House of Representatives have passed law no. 1 of 2023 concerning the latest Criminal Code which will officially take effect in the next 3 years. The latest Criminal Code stipulates cohabitation acts that fall under criminal offenses in accordance with articles 415 and 416 of the latest Criminal Code. Cohabitation (sexual intercourse like husband and wife outside of legal marriage) is considered a criminal act and can be punished by imprisonment. The formulation of the problem in this thesis is what the government considers so that cohabitation is included in one of the articles in the criminal code and how the process of accountability for perpetrators of cohabitation crimes in the criminal code. The research method used is normative. The results of this study prove that the government has passed the latest Criminal Code which in the article also regulates cohabitation acts into criminal acts through many considerations because it is considered not to reflect the customs and culture of the Indonesian nation. Cohabitation is one of the offenses of complaints where the act will only be processed if it is based on complaints from husbands or wives who are victims or aggrieved and can also be reported by parents or children for people who are not bound by marriage.